Beyond SARS-CoV-2: epidemiological surveillance of respiratory viruses in Jalisco, Mexico - Pedroza-Uribe, Isaac Murisi; Vega Magaña, Natali; Muñoz-Valle, José Francisco; Peña-Rodriguez, Marcela; Carranza-Aranda, Ahtziri Socorro; Sánchez-Sánchez, Rocío; Venancio-Landeros, Alberto Anthony; García-González, Octavio Patricio; Zavala-Mejía, Jacob Jecsan; Ramos-Solano, Moisés; Viera-Segura, Oliver; García-Chagollán, Mariel (Frontiers in Public Health, 2024)
Respiratory viral infections represent a significant global health burden. Historically, influenza, rhinovirus, respiratory syncytial virus, and adenovirus have been the prevalent viruses; however, the landscape shifted with the widespread emergence of SARS-CoV-2. The aim of this study is to present a comprehensive epidemiological analysis of viral respiratory infections in Jalisco, Mexico. Data encompassing individuals with flu-like symptoms from July 2021 to February 2023 was scrutinized for viral diagnosis through PCR multiplex. The effect of social mobility on the increase in respiratory viral diagnosis infection was considered to estimate its impact. Additionally, sequences of respiratory viruses stored in public databases were retrieved to ascertain the phylogenetic classification of previously reported viruses in Mexico. SARS-CoV-2 was the most detected virus (n= 5703; 92.2%), followed by influenza (n=479; 7.78%). These viruses were also found as the most common co-infection (n=11; 50%), and for those with influenza, a higher incidence of severe disease was reported (n=122; 90.4%; p <0.001). Regarding comorbidities and unhealthy habits, smoking was found to be a risk factor for influenza infection but a protective factor for SARS-CoV-2 (OR=2.62; IC 95%: 1.66-4.13; OR=0.65; IC 95%: 0.45-0.94, respectively. Furthermore, our findings revealed a direct correlation between mobility and the prevalence of influenza infection (0.214; p<0.001). The study presents evidence of respiratory virus reemergence and prevalence during the social reactivation, facilitating future preventive measures.